Thematic and athematic present endings in Balto-Slavic and Indo-European - Kortlandt, Frederik (Baltistica, 2015)
While the original primary thematic endings were preserved quite well in Balto-Slavic, they were often replaced by the corresponding athematic endings following the thematic vowel *‑e/o‑ in the other Indo-European languages, thus bringing them into line with the secondary endings. Without taking the semantics of the thematic flexion into consideration, Warren Cowgill has forcefully defended the traditional view that apart from the 1st sg. ending *‑ō, the thematic endings were identical with the athematic endings preceded by the thematic vowel *‑e/o‑ in Proto-Indo-European. The main point to be taken into consideration is that the rich and heterogeneous material of Balto-Slavic allows a reconstruction which is on the same level as that of Indo-Iranian and Greek. It confirms the view that our reconstructions have a bias toward the languages on which they are primarily based (Cowgill’s “trusty trio Hittite, Sanskrit, Greek”). The history of linguistic reconstruction shows a gradual shift away from the principal languages.
Keywords: Baltic; Indo-European; historical morphology; verb; thematic endings; athematic endings